Spread of the fascioliasis endemic area assessed by seasonal follow-up of rDNA ITS-2 sequenced lymnaeid populations in Cajamarca, Peru - Bardales-Valdivia, J. N. (2021)
Fascioliasis is a worldwide emerging snail-borne zoonotic trematodiasis with a great spreading capacity linked to animal and human movements, climate change, and anthropogenic modifications of freshwater environments. South America is the continent with more human endemic areas caused by Fasciola hepatica, mainly in high altitude areas of Andean regions. The Peruvian Cajamarca area presents the highest human prevalences reported, only lower than those in the Bolivian Altiplano. Sequencing of the complete rDNA ITS-2 allowed for the specific and haplotype classification of lymnaeid snails collected in seasonal field surveys along a transect including 2007–3473 m altitudes. The species Galba truncatula (one haplotype preferentially in higher altitudes) and Pseudosuccinea columella (one haplotype in an isolated population), and the non-transmitting species Lymnaea schirazensis (two haplotypes mainly in lower altitudes) were found. Climatic seasonality proved to influence G. truncatula populations in temporarily dried habitats, whereas L. schirazensis appeared to be more climatologically independent due to its extreme amphibious ecology. Along the southeastern transect from Cajamarca city, G. truncatula and L. schirazensis shared the same site in 7 localities (46.7% of the water collections studied). The detection of G. truncatula in 11 new foci (73.3%), predominantly in northern localities closer to the city, demonstrate that the Cajamarca transmission risk area is markedly wider than previously considered. Lymnaea schirazensis progressively increases its presence when moving away from the city. Results highlight the usefulness of lymnaeid surveys to assess borders of the endemic area and inner distribution of transmission foci. Similar lymnaeid surveys are still in need to be performed in the wide northern and western zones of the Cajamarca city. The coexistence of more than one lymnaeid transmitting species, together with a morphologically indistinguishable non-transmitting species and livestock movements inside the area, conform a complex scenario which poses difficulties for the needed One Health control intervention.